MENINGKATKAN PRESTASI BELAJAR PPKn TENTANG BELA NEGARA, MELALUI PENERAPAN STRATEGI ADVOKASI - Sumarwoto Sumarwoto (MEDIA DIDAKTIKA, 2019)
PPKn is needed in everyday life to fulfill human needs through solving identifiable problems. The implementation of PPKn needs to be done wisely so that it does not have a negative impact on oneself and the environment. But the reality on the ground, this has not been achieved. Student learning outcomes are still far from the percentage of completeness. Seeing the problems and the importance of the PPKn material as well as the large amount of time allocated in the curriculum in each class, it is necessary to conduct action research by implementing an advocacy learning strategy. This classroom action research was conducted in class IX-B of SMP Negeri 1 Pule Trenggalek. The research was conducted by a PPKn teacher with a collaborator of a class VIII PPKn teacher. The research subjects were all students of class IX-B as many as 30 people consisting of 12 boys and 18 girls. This two-cycle action research study yielded significant results. Through advocacy learning strategies, students' ability to understand state defense can be improved. This can be seen from the results of the post test. The application of an advocacy learning strategy in PPKn lessons begins with forming a group to discuss a problem. The results of the small group are presented to the large group, before being presented in front of the class.